Design estratégico e design de moda: construção de princípios metodológicos para o estudo de tendências - Visoná, Paula Cristina (Universidade do Vale do Rio dos Sinos, 2010)
The following research presents the construction of a method for trend studies based on the strategic design methodological procedures and the concept of intertextuality. It intends to approach in a transdisciplinary way the emerging signs from the sociocultural environment, anticipating the representative signals of constituent change of trends in order to work towards the development of projectual strategies. It considers the understanding that the anticipation of emerging signs from the sociocultural environment allows the identification of trends and the improvement of strategical decisions, contributing the creation of dialog between organizations, individuals and design artefacts. The communicability perspective between representation instances of subjectivities such as art, film, fashion, etc is essential for this study, and its theoretical and methodological unfolding allows the framing of the tools that constitutes the proposed method.
Keywords: Design; Design estratégico; Moda; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial